Pengaruh Perputaran Kas, Perputaran Piutang, dan Perputaran Persediaan terhadap Rentabilitas pada PT. Cipta Karya Makmur Bersama di Kota Makassar. - Asniwati Asniwati; Adrianah Adrianah; Yusra Nginang (Pascasarjana STIE Amkop Makassar, 2021)
Abstrak The Effect of Cash Turnover, Receivables Turnover and Inventory Turnover Rates on Profitability at PT. Cipta Karya Makmur Bersama in the city of Makassar. This study aims to determine the effect of the level of cash turnover, accounts receivable, and partially and simultaneously a significant effect on profitability at PT. Cipta Karya Makmur Bersama 2015-2019 in the city of Makassar The main problem in this research is whether the level of cash turnover, receivables, and inventory partially and simultaneously has a significant effect on profitability at PT. Cipta Karya Makmur Bersama 2015-2019 in the city of Makassar. The results of this study indicate that the variable cash turnover has a significant effect on rentability because it has a significance value of 0,000 which is smaller than a = 0.05, accounts receivable turnover variable has a significant effect on rentability because it has a significance value of 0.003 which is smaller than a = 0, 05, while the inventory turnover variable does not have a significant effect on profitability because it has a significance value of 0.408 which is greater than a = 0.05 Simultaneously the cash turnover, accounts receivable, and inventory have a significant effect on rentability because it has a significance value of 0.001 which is smaller than a = 0.05.Kata Kunci: Cash Turnover, Receivable Turnover, Inventory Turnover and Profitability